Genomic, Biochemical, and Modeling Analyses of Asparagine Synthetases from Wheat - Xu, Hongwei; Curtis, Tanya Y.; Powers, Stephen J.; Raffan, Sarah; Gao, Runhong; Huang, Jianhua; Heiner, Monika; Gilbert, David R.; Halford, Nigel G. (Frontiers in Plant Science, 2018)
Asparagine synthetase activity in cereals has become an important issue with the discovery that free asparagine concentration determines the potential for formation of acrylamide, a probably carcinogenic processing contaminant, in baked cereal products. Asparagine synthetase catalyses the ATP-dependent transfer of the amino group of glutamine to a molecule of aspartate to generate glutamate and asparagine. Here, asparagine synthetase-encoding polymerase chain reaction products were amplified from wheat (Triticum aestivum) cv. Spark cDNA. The encoded proteins were assigned the names TaASN1, TaASN2 and TaASN3 on the basis of comparisons with other wheat and cereal asparagine synthetases. Although very similar to each other they differed slightly in size, with molecular masses of 65.49, 65.06 and 66.24 kDa, respectively. Chromosomal positions and scaffold references were established for TaASN1, TaASN2 and TaASN3, and a fourth, more recently identified gene, TaASN4. TaASN1, TaASN2 and TaASN4 were all found to be single copy genes, located on Chromosomes 5, 3 and 4, respectively, of each genome (A, B and D), although variety Chinese Spring lacked a TaASN2 gene in the B genome. Two copies of TaASN3 were found on Chromosome 1 of each genome, and these were given the names TaASN3.1 and TaASN3.2. The TaASN1, TaASN2 and TaASN3 PCR products were heterologously-expressed in Escherichia coli (TaASN4 was not investigated in this part of the study). Western blot analysis identified two monoclonal antibodies that recognised the three proteins, but did not distinguish between them, despite being raised to epitopes SKKPRMIEVAAP and GGSNKPGVMNTV in the variable C-terminal regions of the proteins. The heterologously-expressed TaASN1 and TaASN2 proteins were found to be active asparagine synthetases, producing asparagine and glutamate from glutamine and aspartate. The asparagine synthetase reaction was modelled using SNOOPY® software and information from the BRENDA database to generate differential equations to describe the reaction stages, based on mass action kinetics. Experimental data from the reactions catalysed by TaASN1 and TaASN2 were entered into the model using Copasi, enabling values to be determined for kinetic parameters. Both the reaction data and the modelling showed that the enzymes continued to produce glutamate even when the synthesis of asparagine had ceased due